4/3x-4=x+4

Simple and best practice solution for 4/3x-4=x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/3x-4=x+4 equation:



4/3x-4=x+4
We move all terms to the left:
4/3x-4-(x+4)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
We get rid of parentheses
4/3x-x-4-4=0
We multiply all the terms by the denominator
-x*3x-4*3x-4*3x+4=0
Wy multiply elements
-3x^2-12x-12x+4=0
We add all the numbers together, and all the variables
-3x^2-24x+4=0
a = -3; b = -24; c = +4;
Δ = b2-4ac
Δ = -242-4·(-3)·4
Δ = 624
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{624}=\sqrt{16*39}=\sqrt{16}*\sqrt{39}=4\sqrt{39}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-24)-4\sqrt{39}}{2*-3}=\frac{24-4\sqrt{39}}{-6} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-24)+4\sqrt{39}}{2*-3}=\frac{24+4\sqrt{39}}{-6} $

See similar equations:

| -71+-20b=389 | | .2/x=4 | | g/4+17=24 | | f7−25=−29 | | 14.2/x=4 | | -4(j-17)=-8 | | 10x+12=4x+42 | | f7−25=−29f= | | 14=4/x+10 | | 19b-20b+6=-5 | | 2y+–9=11 | | 2.3-0.5a=2.4 | | -4(x-12)=8 | | a/2-5=-7 | | 1.7+4q=12.1 | | 18u+5u-12u=-11 | | 20.5=a-1.5 | | 5(-3x-2)-(×-3)=-4(4x+5)+13 | | -7r+1=-55 | | 3x+2=2x+4=4x-2 | | 8r-5=75 | | 4n+6−2n=−2 | | -(x-5)=-1 | | 4(u-15)+10=14 | | 1.1=2s-10.9 | | -121+11x=-3x+117 | | 54+19w=605 | | X-(x(.10))=1320 | | −40=10-10s10−10s | | -5+5r=-45 | | -533=52-15n | | 7+10x=107 |

Equations solver categories